CONSIDERATION OF LABOR DISPUTES BY THE COURTS IN THE UZBEK SSR (European Science Methodical Journal, 2024)
In this article, on the eve of fascist Germany's attack on the Soviet Union, the militarization of enterprises and institutions, the restriction of the constitutional right of citizens to freely choose a profession and work, the brutal exploitation of the population, and the use of tens of thousands of prisoners as free labor by the authoritarian Soviet regime are revealed on the example of the Uzbek SSR. Also, the article highlights the fact that judges became victims of repression, the strengthening of party and government control over the judicial system based on archival sources.